Legal Protection for Boarding House Owners for The Transfer of Rent to a Third Party (Study on 8888 Boarding House in North Sumatra) - Luthfi Siregar, Muhammad; Bawono, Bambang Tri (UNISSULA Semarang, 2025)
In everyday life, as social beings, humans always interact with other humans to meet their needs, especially students. Students who pursue education come not only from educational centers but also from various regions. Residents living in the surrounding area take advantage of this opportunity to start businesses by temporarily renting out their buildings and residences, including rooms. The type of research used in this study is legal research, using an empirical juridical legal research approach. Empirical legal research takes the form of community legal behavior. The data source for empirical legal research is not based on written positive law, but rather on observations at the research location. The binding relationship is based on the provisions of Article 1548 of the Civil Code, first between the boarding house owner and the tenant, second between the tenant and a third party. The relationship that occurs between the boarding house owner and the tenant occurs legally based on an agreement to enter into a rental agreement for the object of the rental, namely the boarding house owned by the boarding house owner himself, and the second relationship that occurs is between the tenant and the third party. The legal consequences arising from the transfer or re-renting of the Boarding House for the parties based on the provisions of Article 1267 of the Civil Code are that the owner of the boarding house has the right to immediately terminate the agreement and can cancel the agreement that was made by the parties and ask for compensation, as a result of the cancellation of the Boarding House rental agreement, the rental agreement made by the tenant with the third party is also null and void by law. Efforts made to resolve the rental of this Boarding House are carried out by taking action independently and through deliberation.